2005
DOI: 10.1001/archpsyc.62.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Regionally Specific Disturbance of Dorsolateral Prefrontal–Hippocampal Functional Connectivity in Schizophrenia

Abstract: Our results suggest a regionally specific alteration of HF-DLPFC functional connectivity in schizophrenia that manifests as an unmodulated persistence of an HF-DLPFC linkage during working memory activation. Thus, a mechanism by which HF dysfunction may manifest in schizophrenia is by inappropriate reciprocal modulatory interaction with the DLPFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
322
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 534 publications
(378 citation statements)
references
References 55 publications
(69 reference statements)
48
322
2
6
Order By: Relevance
“…Consistently, hippocampal disinhibition disrupts hippocampus-dependent rapid place learning performance, as well as aspects of attentional performance that do not normally require the hippocampus, but are mediated by prefrontal-striatal mechanisms. The latter supports that hippocampal dysfunction may partly manifest through deficits in prefrontal-dependent function, consistent with strong hippocampo-prefrontal functional connectivity (Meyer-Lindenberg et al 2005;Bast 2011). The attentional and memory deficits caused by hippocampal neural disinhibition, together with findings that prefrontal-cortical disinhibition disrupts attentional and executive functions (Gruber et al 2010;Enomoto et al 2011;Paine et al 2011;Pehrson et al 2013;Pezze et al 2014;Paine et al 2015;Tse et al 2015), highlight the importance of cortico-hippocampal GABAergic inhibition for cognitive function.…”
Section: Resultssupporting
confidence: 59%
“…Consistently, hippocampal disinhibition disrupts hippocampus-dependent rapid place learning performance, as well as aspects of attentional performance that do not normally require the hippocampus, but are mediated by prefrontal-striatal mechanisms. The latter supports that hippocampal dysfunction may partly manifest through deficits in prefrontal-dependent function, consistent with strong hippocampo-prefrontal functional connectivity (Meyer-Lindenberg et al 2005;Bast 2011). The attentional and memory deficits caused by hippocampal neural disinhibition, together with findings that prefrontal-cortical disinhibition disrupts attentional and executive functions (Gruber et al 2010;Enomoto et al 2011;Paine et al 2011;Pehrson et al 2013;Pezze et al 2014;Paine et al 2015;Tse et al 2015), highlight the importance of cortico-hippocampal GABAergic inhibition for cognitive function.…”
Section: Resultssupporting
confidence: 59%
“…Relative to the DLPFC, the possible role of VLPFC abnormalities in schizophrenia has received little attention. We are not aware of any studies reporting increased temporal-VLPFC connectivity, although it occurred at subthreshold levels in one study described above (Meyer-Lindenberg et al, 2005, supplementary online data). While both groups in the current study activated VLPFC equally (Ragland et al, 2005), as in Jennings et al (1998) and Barch et al (2001), other studies have found increased task-related activity of VLPFC in schizophrenia (Kim et al, 2003;Bonner-Jackson et al, 2005;Tan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The same concern arises with regard to a possible non-specific increase in VLPFC correlations. In order to assess whether the observed group differences in connectivity were indeed selective for temporal-prefrontal circuits, we generated "reverse direction" correlation maps (see also Meyer-Lindenberg et al, 2005), taking as seed ROIs the two prefrontal clusters exhibiting significant group differences, and examining correlations with all voxels in the brain. Connectivity with the DLPFC region was not diffusely increased in controls, but as expected showed greater connectivity primarily in left temporal lobe, with significant (P < 0.05 cluster-corrected) group differences in regions overlapping the STG and the PHIP.…”
Section: Group Differences In Connectivitymentioning
confidence: 99%
“…The pathophysiology of schizophrenia involves distributed functional dysconnectivity involving a number of brain regions, 1,2 including the frontal lobe, [3][4][5][6][7][8][9][10] and its language-related areas in the inferior frontal gyrus, 11,12 sensory-motor areas, 13 the temporal lobe, 14 limbic structures, 15,16 and thalamus. [17][18][19][20][21][22][23][24] Despite numerous leads, the reported findings are somewhat inconsistent and the core regions associated with the pathogenesis of schizophrenia still remain controversial.…”
Section: Introductionmentioning
confidence: 99%